Pelvic Rib: Developmental Anomaly, A Case Report - Hakan Tuna; Nurettin Taştekin; Ercüment Ünlü; Tevfik Fikret Çermik; Kenan Sarıdoğan (Archives of Rheumatology, 2008)
Pelvic rib is a rare and benign developmental abnormality. It typically appears as a rib or phalanx-like bone in radiological evaluation. Cortical type bone is pronounced in its structure and pseudo-articulation can exist. It is generally asymptomatic and does not require surgical treatment. In differential diagnosis, myositis ossificans and avulsion injury must be ruled out. In our case, this developmental abnormality was identified accidentally by radiographic evaluation of a patient who had trauma. Therefore, pelvic rib should be remembered in differential diagnosis of developmental skeletal abnormalities. (Rheumatism 2008; 23:151-3)